EDUCATION OF BALANCED NUTRITION FOR MAINTAINING REPRODUCTIVE HEALTH IN MENOPAUSE WOMEN - Naimah Nasution; Erlina Hayati; Peny Ariani (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Menopause is a natural phase experienced by women aged 45–55 years due to the cessation of ovarian function, resulting in a decrease in the hormones estrogen and progesterone. This condition causes changes in reproductive, mental, and physical health that affect quality of life. Therefore, balanced nutrition is needed to keep their reproductive health, mood and physical endurance. If left untreated, this can reduce self-confidence and affect social and family relationships. This community service activity was held on May 13, 2026, in Hamlet 5, Patumbak 1 Village, with the aim of raising awareness about the importance of balanced nutrition in maintaining the reproductive health of menopausal women. Education was conducted through lectures, discussions, and interactive Q&A sessions. The material covered understanding menopause, the physiological changes that occur, and the role of balanced nutrition as a promotive-preventive strategy. Nutrients emphasized included calcium for bone density, vitamin D for metabolism, protein for muscle strength, fiber for digestion, and phytoestrogens for reducing vasomotor symptoms. Results showed that participants were able to understand the concept of menopause and recognize the contribution of balanced nutrition in reducing symptoms and supporting reproductive health. Nutrition education has been proven to increase knowledge and encourage the adoption of healthy eating patterns, which play a role in preventing long-term complications such as osteoporosis, heart disease, diabetes mellitus, and hypertension. It is recommended that similar activities be carried out on an ongoing basis, involving local health workers and community leaders to strengthen awareness and program sustainability.